Поетичний дивосвіт Миколи Вороного - Колкутина, В.В. (Культура народов Причерноморья, 2004)
В статье рассматривается поэтический мир одного из основоположников украинского модернизма начала ХХ столетия – Николая Вороного.
Внутренний мир поэта-модерниста суголостен западноевропейской философско-литературной мыслью, с творчеством П. Верлена и Ш. Бодлера, с русским символизмом – К. Бальмонтом и А. Белым. В статье автор доказывает и аргументирует своеобразное поэтическое мировоззрение Н. Вороного на материале его лирического цикла “De mortuis”. The article deals with the poetical world of one of the founders of the Ukrainian modernism of the beginning of the 20th century, Nicolay Voronoy.
The poet-modernist’s inner west-European philosophical-literary thought, with P.Vernen’s and S.Bodler’s work, with the Russian symbolism - C.Balmond and A.Beliy.in this article the author proves and agues N.Voronoy peculiar poeti-cal outlook on the basis of his lyrical series “De mortuis”.